Perioperative clinical utility of myocardial deformation imaging: a narrative review. (October 2019) - Abuelkasem, Ezeldeen; Wang, David W.; Omer, Mohamed A.; Abdelmoneim, Sahar S.; Howard-Quijano, Kimberly; Rakesh, Hulimangala; Subramaniam, Kathirvel
Summary: Preoperative cardiac function is an important predictor of postoperative outcomes. Patients with heart failure are at higher risk of perioperative morbidity and mortality. Left ventricular ejection fraction, derived by standard echocardiography, is most frequently used to assess cardiac function in the intraoperative and postoperative periods. Myocardial strain analysis, a measurement of myocardial deformation, can provide additional information to left venricular eject fraction estimation. Here, we provide an overview of myocardial strain and different methods used to evaluate strain, including speckle tracking echocardiography. Speckle tracking echocardiography is an imaging modality that can analyse and track small segments of the myocardium, which provides greater detail for assessing global and regional cardiac motion and function. We further review the literature to illustrate the value of speckle tracking echocardiography-derived myocardial strain in describing cardiac function and its association with adverse surgical outcomes in the perioperative period, including low cardiac output states, need for inotropic support, postoperative arrhythmias, subclinical myocardial ischaemia, and length of hospital stay.